Empathy in Piano Duet Rehearsal and Performance: A Response to Haddon and Hutchinson - Seddon, Fred (Empirical Musicology Review, 2015)
This review comments upon the article entitled above. The article is well written and describes an interesting and original study. This review critiques the Method and Discussion sections of the article and offers suggestions for future research. Three specific points from the method are considered relating to: dual roles as researcher-musicians, the use of reflective diaries in research, and the impact on the research of the prior relationship between the authors. The unique role of “written empathy” is discussed within the context of empathic relationships. Also, this review considers how shifts from verbal to non-verbal communication may indicate movement from a “top-down” to “bottom up” response, and how this shift is related to “empathetic attunement.”